“What Is Critical Geography, What Can, and What Must It Be?”: A Continuing Conversation - Klosterkamp, Sarah; Sheringham, Olivia (ACME, 2026)
We return to the question “What is critical geography, what can, and what must it be?” as an ongoing and collective problem and provocation. Taking the ACME Editorial Collective’s “Unpause-ish Statement” as a starting point, we situate this conversation within a conjuncture of overlapping crises that are reshaping both the worlds we study and the conditions under which we produce knowledge. Bringing together five contributions from the 2025 RGS–IBG panel, we trace how critical geography is being reworked across struggles over labour, care, method, and political responsibility. These interventions confront the co-optation of social justice, the urgency of responding to anti-trans violence, the possibilities of speculative and reparative approaches, and the importance of centring situated, embodied, and everyday practices of resistance and survival. Across all five, critical geography emerges as a contested praxis that must continually turn critique inward as well as outwards. We argue that critical geography must make its own conditions of labour visible, remain accountable to those most affected by injustice, and expand what counts as scholarship, method, and intervention. This is not a call to define the field, but to keep it open: to unpause without rushing, to refuse without withdrawing, and to insist on forms of critique that are inseparable from care, responsibility, and collective world-making.